Characterization of mouse di-N-acetylchitobiase that can degrade chitin-oligosaccharides. Issue 12 (1st December 2020) - Ohno, Misa; Miyazaki, Masao; Kimura, Masahiro; Minowa, Yusaku; Sakaguchi, Masayoshi; Oyama, Fumitaka; Yamashita, Tetsuro
ABSTRACT: Di- N -acetylchitobiase (Ctbs) degrades β-1, 4 glycoside bonds of the chitobiose core of free asparagine-linked glycan. This study examined whether Ctbs degrades chitin-oligosaccharides to GlcNAc in mammals. We analyzed Ctbs mRNA and protein expression in mouse tissues and characterized enzymatic activity using recombinant mouse Ctbs expressed in Escherichia coli . Ctbs mRNA and protein were expressed in various tissues of mouse, including the stomach. Optimal conditions for recombinant Ctbs were pH 3.0 and 45°C, and the recombinant enzyme was retained more than 94% activity after incubation at pH 3.0–7.0 and below 37°C. The recombinant Ctbs hydrolyzed (GlcNAc)3 and (GlcNAc)6 at pH 3.0 and produced GlcNAc. The K m of Ctbs was lowest with (GlcNAc)3 as a substrate. k cat / K m was fourfold as high with (GlcNAc)3 and (GlcNAc)4 as substrates than with (GlcNAc)2 . These results suggest that Ctbs digests chitin-oligosaccharides or (GlcNAc)2 of reducing-end residues of oligosaccharides and produces GlcNAc in mouse tissues. GRAPHICAL ABSTRACT: uf0001 Di- N -acetylchitobiase (Ctbs) is most active at pH 3.0 and retained more than 94% activity after incubation at pH 3.0–7.0 and below 37°C. The preferred substrate of recombinant Ctbs is (GlcNAc)3 .